Analisis Yuridis Terhadap Peralihan Hak Atas Tanah Dalam Perjanjian Jual Beli Tanah Akibat Adanya Cacat Kehendak (Willsgebrek) (Analisis Putusan Nomor 71/PDT/2016/PT.DPS) - Vannyana Albert (Iuris Studia: Jurnal Kajian Hukum, 2022)
In practice, events often occur that indicate one of the defects of the will such as oversight, deception and coercion. However, it cannot also be said that the occurrence of the statement of will that agreed to the agreement was flawless. The research method used in this research is normative juridical research, which is supported by primary and secondary data sources, and qualitative analysis is carried out. The results of the research and discussion are the provisions of customary law regarding the transfer of land rights where someone who wants to transfer their land rights to those who want to be transferred in front of the village head, then in civil law, if the delivery of the goods requires a juridical handover (Juridische Levering) in addition to handover (Eitel Jke Levering) in order for the buyer's ownership to be perfect, the buyer must complete the delivery (Article 1475 of the Civil Code). In the provisions of agrarian law that the transfer of land rights is contained in Article 37 paragraph (1) Government Regulation no. 24 of 1997 concerning Land Registration. Determine if there is a defect of will even though it is in accordance with Article 1320 of the Civil Code, namely by using the principle of good faith. The judge's consideration in Decision Number 71/Pdt/2016/PT.DPS, where the judge sees from the principle of freedom of contract as reflected in the provisions of Article 1338 paragraph (1) of the Civil Code determines that all agreements made legally apply as law for those who make it. The non-fulfillment of this principle is because the agreement was made when I Rantuh was sick and under pressure so that he could not give an agreement freely, meaning that these reasons were the justification for the Supreme Court to cancel the PPJB because the agreement was contrary to the provisions of Article 1320 of the Civil Code